Compressive buckling of simply supported curved plates and cylinders of sandwich construction - Stein, Manuel (National Advisory Committee for Aeronautics, 1952)
Theoretical solutions are presented for the buckling in uniform axial compression of two types of simply supported curved sandwich plates: the corrugated-core type and the isotropic type. Results are given in the form of equations and curves.
"January 1952."
NACA TN No. 2601.
Keywords: Plates (Engineering) -- Curvature.; Cylinders.; Sandwich construction.; Buckling (Mechanics); Loads (Mechanics); Strains and stresses.; elektronické knihy; electronic books